To Teach Higher Education Students the Method of Organizing Non-Traditional Lessons Based on the Nature and Structure of Music Culture Lessons - Dusmatova Malika Odiljonovna (Research Parks Publishing LLC, 2021)
Any science is a collection of knowledge about the laws of society and the development of thinking. In order for science to stand out and function, it must have its own structure. This article is devoted to the method of organizing non-traditional lessons for higher education students based on the nature and structure of music culture lessons.